EXPEDIENTE - v18n1 - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Jacó Vilela, Ana Maria; Mendes, Deise Maria Leal Fernandes; Quadros, Laura Cristina de Toledo; Valentim, Renata Patrícia Forain de; Darriba, Vinicius Anciães (Estudos e Pesquisas em Psicologia, 2018)
EXPEDIENTE - v18n1